2010
DOI: 10.1007/978-3-642-04231-7_11
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Lung Cancer Survivorship

Abstract: A lung cancer diagnosis and associated therapeutic management is associated with unique and varying degrees of adverse physical/functional impairments that dramatically reduce a patient's ability to tolerate exercise. Poor exercise tolerance predisposes to increased susceptibility to other common age-related diseases, poor quality of life (QOL), and likely premature death. Here we review the putative literature investigating the role of exercise as an adjunct therapy across the lung cancer continuum (i.e., dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 80 publications
(104 reference statements)
0
17
0
1
Order By: Relevance
“…Two recent systematic reviews examined the role of exercise in the care of patients with lung cancer across the illness trajectory and the results were promising for the use of exercise as an adjunct treatment among patients with both early and advanced stages of illness 68,69 . One study examined the use of exercise in combination with relaxation for patients with advanced lung cancer using a hospital based supervised group exercise along with a concurrent home based exercise program 70 .…”
Section: Discussionmentioning
confidence: 99%
“…Two recent systematic reviews examined the role of exercise in the care of patients with lung cancer across the illness trajectory and the results were promising for the use of exercise as an adjunct treatment among patients with both early and advanced stages of illness 68,69 . One study examined the use of exercise in combination with relaxation for patients with advanced lung cancer using a hospital based supervised group exercise along with a concurrent home based exercise program 70 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, provision of the appropriate treatment and care programs for controlling the disease and improving the patient QOL remains a fundamental issue. A multidimensional therapeutic approach is recommended including pulmonary rehabilitation (6,7) and an adequate level of physical activity (8,9) in order to improve exercise tolerance, health-related QOL as well as surgical candidacy and to decrease surgical morbidity. Recent studies have shown that physical activity may have important benefits on lung cancer patients and survivors (10)(11)(12), regardless of the disease stage (13) or limited physical activity (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Engagement in physical activity, both during treatment and in survivorship, can confer important benefits, including enhanced quality of life and physical function and reduced symptom burden [26]. Despite this empirical evidence, and growing awareness amongst health professionals, many cancer survivors do not engage in recommended levels of physical activity [1].…”
Section: Introductionmentioning
confidence: 99%